2008
DOI: 10.1074/jbc.m709972200
|View full text |Cite
|
Sign up to set email alerts
|

The Sphingolipid Long-chain Base-Pkh1/2-Ypk1/2 Signaling Pathway Regulates Eisosome Assembly and Turnover

Abstract: Eisosomes are recently described fungal structures that play roles in the organization of the plasma membrane and endocytosis. Their major protein components are Pil1 and Lsp1, and previous studies showed that these proteins are phosphorylated by the sphingolipid long-chain base-activated Pkh1 and Pkh2 protein kinases in vitro. We show that Pkh1 and Pkh2 phosphorylate Pil1 and Lsp1 in vivo to produce species B, and that heat stress, which activates Pkh1 and Pkh2, generates a more highly phosphorylated species,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
163
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(177 citation statements)
references
References 42 publications
12
163
2
Order By: Relevance
“…Moreover, Pil1 and Lsp1 are differentially phosphorylated in re-sponse to an increase of long-chain bases, which are the precursors of sphingolipids, by Pkh1/2, two kinases that localize to eisosomes (Zhang et al, 2004;Walther et al, 2007;Luo et al, 2008). Perturbation of the Pil1 phosphorylation status affects Pil1 assembly into eisosomes: specifically, eisosomes disassemble if Pil1 is hyperphosphorylated, and more Pil1 assembles into eisosomes if Pil1 is hypophosphorylated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Pil1 and Lsp1 are differentially phosphorylated in re-sponse to an increase of long-chain bases, which are the precursors of sphingolipids, by Pkh1/2, two kinases that localize to eisosomes (Zhang et al, 2004;Walther et al, 2007;Luo et al, 2008). Perturbation of the Pil1 phosphorylation status affects Pil1 assembly into eisosomes: specifically, eisosomes disassemble if Pil1 is hyperphosphorylated, and more Pil1 assembles into eisosomes if Pil1 is hypophosphorylated.…”
Section: Discussionmentioning
confidence: 99%
“…Long chain bases also regulate the phosphorylation of the primary components of the eisosome, Pil1 (phosphorylation inhibited by long chain bases) and Lsp1 (long chain bases stimulate phosphorylation). Appearance of membrane-associated eisosomes drastically changes in response to Pil1 hyper-or hypophosphorylation [16,34]. Whether and how these changes in eisosome morphology influence the furrow-like invaginations of the plasma membrane (MCC) is not yet known.…”
Section: Role Of Lipidsmentioning
confidence: 99%
“…One possibility is that striation variability may reflect a switch in "levels of engagement" between the eisosomal lipids and their underlying organizing systems. If this is the case, the variability could be a morphological reflection of (some of) the signal transduction properties attributed to eisosomes (19,20,22). Walther and colleagues (30,83) have suggested analogies between eisosomes and caveolae.…”
Section: Discussionmentioning
confidence: 99%
“…These observations were brought together by Strádalová et al (5), who showed that the membrane compartment occupied by Can1p (MCC) localized to the invaginations seen with freeze fracture EM, and by Karotki et al (6), who showed that Pil1p localizes to the cytoplasmic surfaces of these invaginations. Additional proteins also associate with these punctate domains, in some cases in a transient fashion (17), and the MCC component is reportedly enriched in ergosterol (18) and influenced by phosphoinositide (6,19,20) and sphingolipid (14,17,(21)(22)(23)(24) levels. Hence, the current yeast model (25,26) proposes that Pil1p and Lsp1p, which contain membrane curvatureinducing BAR domains (6,27,28), together with Seg1p (29,30), form a submembrane complex (6) reportedly influenced by Pil1p phosphorylation (25); this complex then either creates or associates with the MCC domains, presumably inducing an inward curvature.…”
mentioning
confidence: 99%